Investigating Laser Direct Structuring and Aerosol-Jet for Additively Manufactured Helix Antennas - Ankenbrand, Markus; Panusch, David; Piechulek, Niklas; Gold, Gerald; Helmreich, Klaus; Franke, Jörg (2024 International Conference on Electronics Packaging, ICEP 2024, 2024)
This paper investigates the manufacturing of helix antennas using additive technologies, highlighting the influences of substrate surface quality and manufacturing processes on antenna characteristics. The focus lies on Fused Filament Fabrication and Digital Light Synthesis for the substrate generation, and Aerosol-Jet and Laser Direct Structuring (LDS) for functional structuring. The tested materials are PEEK, epoxy and polycarbonate for the substrate and silver and copper for the traces. Challenges encountered during manufacturing include spreading of the ink in Aerosol-Jet printing, and short circuits caused by smoke residues in LDS. The radiation patterns of the additively manufactured antennas are compared with simulated responses and a subtractively manufactured reference, revealing a small but measurable impact of geometric deviations and surface roughness on performance.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Additive Manufacturing; Helix Antenna; Laser Direct Structuring; Printed Electronics